Variation of chart datum towards maritime delimitation due to rising sea level - Mohd. Faizuddin Abd. Rahman, 1991-, author; Mohd. Razali Mahmud, supervisor; Fakulti Alam Bina dan Ukur (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Sarjana Falsafah) - Universiti Teknologi Malaysia, 2018